The Effect of Investment, National Government Expenditure, Exports, and Imports on Indonesia’s Economic Growth - daniel eka bonokeling; Maimun Sholeh; Mispandi Mispandi (Jurnal Ekonomi dan Pembangunan, 2022)
This study aims to see the effect of investment, government expenditure, exports, and imports on Indonesia’s economic growth. The type of this research is quantitative. This research was conducted using secondary data published by the World Bank. The data technique used is the documentation method. The data were analyzed through the Error Correction Model (ECM). The research period was annually from 1960 to 2018. The results of this study indicate as follows. (1) in the long term, investment negatively and significantly affects Indonesia’s economic growth with a value of -0.02% with a significance value (p) < 0.05; in the short term, investment negatively and insignificantly affects Indonesia’s economic growth with a value of -0.001% with a significance value (p) < 0.05. (2) In the long term, government control positively and significantly affects Indonesia’s economic growth by 7.75% with a significance value (p) < 0.05; in the short term, government spending positively and significantly affects Indonesia’s economic growth by 7.75% with a significance value (p) < 0.05. (3) In the long run, exports negatively and insignificantly affect Indonesia’s economic growth by 0.12% with a significance value (p) < 0.05; in the short term, exports are negatively and significantly affected by -0.93% with a significance value (p) < 0.10. (4) In the long term, imports positively and significantly affect economic growth by 1.53% with a significance value (p) < 0.05; then, in the short term, imports also positively and significantly affect economic growth by 1.57% with a significance value (p) < 0.05. (5) Simultaneously, investment, government expenditure, exports, and imports positively and significantly impact Indonesia’s economic growth, with an F- statistic value of 0.0000.